2020
DOI: 10.1080/21623945.2020.1735025
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of ligated vessels promote the retention and regeneration of free fat: constructing a fat flap in tissue engineering chamber

Abstract: Background: Breast reconstruction with fat grafting has an unstable retention rate due to insufficient revascularization. Tissue Engineering Chamber (TEC) model can promote tissue regeneration in the chamber by introducing ligated vessels around the tissue. We introduced ligated vessels with free fat graft to investigate the retention rate and revascularization of grafted fat that in TEC model. Methods: SD rats (n=24) was divided into 3 groups randomly. Group A: Standard TEC model was constructed; Group B: the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…A further challenge to the TEC method was made by Lei et al 26 They inserted ligated vessels with fat grafts into a chamber, using fat grafts instead of less available native flaps. This study demonstrated that ligated vessels can serve as a nourishing source to fat flap creation inside a TEC.…”
Section: Tissue Engineering Chambermentioning
confidence: 99%
“…A further challenge to the TEC method was made by Lei et al 26 They inserted ligated vessels with fat grafts into a chamber, using fat grafts instead of less available native flaps. This study demonstrated that ligated vessels can serve as a nourishing source to fat flap creation inside a TEC.…”
Section: Tissue Engineering Chambermentioning
confidence: 99%
“…These drawbacks can be resolved by restoration of the breast shape through tissue engineering. Formation of a stable soft tissue on the recipient site requires sufficient vascularization and adipose tissue regeneration [ 2 , 3 ], and this is a major challenge in breast tissue engineering. Stem cells act as seed cells in tissue engineering whereby they can regenerate expected tissue via direct differentiation into proper cell type and paracrine regulation [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%